PENGETAHUAN LAPORAN KEUANGAN PEMILIK UMKM SENTRA MEBEL DI JAWA TIMUR - Susanti, Ari; Ismunawan, Ismunawan (JAB (Jurnal Akuntansi & Bisnis), 2018)
Financial reports are very important in SME activities, financial statements can be used by business owners in decision making. This research is to find out how the knowledge of SME practitioners. The purpose of this study was to analyze the effect of education, business scale, company age, financial knowledge in financial statements. The study population was SME entrepreneurs in furniture centers in East Java. Data collection was conducted by field survey using a questionnaire. Methods of data analysis using SPSS Version 21. The results of the study concluded that education, business scale, company age, financial knowledge and experience in financial statements. Keywords: Financial Knowledge, SME Owners